Relación entre construcción de identidad de género femenino y cambios corporales en mujeres transgénero de la ciudad de Cali - Ángel Chates, Yina Lizeth (Universidad de San Buenaventura - Cali, 2017)
In this article from a feminist constructivist theory the relationship between the construction of female identity and body changes transgender women understood. He proposed an approach to the experiences of three transgender women allowing them to show their contexts of life, expose gender inequalities and empower social change. It was evident that gender identity is conceived as a social construction, which exists in the socially constructed interactions and body changes have become the means to express what every woman feels about transgender identity.